Unraveling heterogeneity of consumers’ food choice: Implications for nutrition interventions in eastern India - Custodio, Marie Claire; Ynion, Jhoanne; Samaddar, Arindam; Cuevas, Rosa Paula; Mohanty, Suva Kanta; Ray (Chakravarti), Anindita; Demont, Matty (Elsevier, 2021)
Understanding heterogeneity of consumers' food choice is critical in formulating tailored nutrition interventions. To illustrate this, we survey urban and rural consumers from low- and middle-income households in eastern India to unravel five sources of heterogeneity (5 Ws) in gastronomic systems that affect diets: (i) socioeconomic characteristics of the target population (who); (ii) food environments (where); (iii) eating occasions (when); (iv) consumed dishes (what); and (v) ingredient attributes and consumer attitudes towards food (why). Diets in eastern India are predominantly starch-based featuring infrequent intake of fruits and vegetables. Accounting for heterogeneity in gastronomic systems can help policy makers and nutritionists develop more targeted nutrition interventions, which can aid in the development of planetary health diets in various contexts around the world.